Micro- and Nano-Fabrication by Metal Assisted Chemical Etching - Romano, Lucia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Metal-assisted chemical etching (MacEtch) has recently emerged as a new etching technique capable of fabricating high aspect ratio nano- and microstructures in a few semiconductors substrates-Si, Ge, poly-Si, GaAs, and SiC-and using different catalysts-Ag, Au, Pt, Pd, Cu, Ni, and Rh. Several shapes have been demonstrated with a high anisotropy and feature size in the nanoscale-nanoporous films, nanowires, 3D objects, and trenches, which are useful components of photonic devices, microfluidic devices, bio-medical devices, batteries, Vias, MEMS, X-ray optics, etc. With no limitations of large-areas and low-cost processing, MacEtch can open up new opportunities for several applications where high precision nano- and microfabrication is required. This can make semiconductor manufacturing more accessible to researchers in various fields, and accelerate innovation in electronics, bio-medical engineering, energy, and photonics. Accordingly, this Special Issue seeks to showcase research papers, short communications, and review articles that focus on novel methodological developments in MacEtch, and its use for various applications.